EFEKTIVITAS PENYELESAIAN PEMBIAYAAN BERMASALAH MURABAHAH DENGAN KEBIJAKAN RESCHEDULING PADA BAITUL MAAL WAT TAMWIL (BMT) AS’ADIYAH SENGKANG - Sitti Asia; Ismail Keri (Institut Agama Islam Negeri (IAIN) Bone, 2021)
Murabahah financing problems that occurred at BMT As'adiyah Sengkang in 2017 to 2021 continued to increase this was due to the business being undertaken by customers decreased in terms of production and consumption so that it also affected customer income which decreased. In responding to this, the BMT As'adiyah Sengkang took a rescheduling policy for the non-performing Murabahah financing so that the financing of customers who had failed to pay could return smoothly.This type of research is a field research with a qualitative research approach. The data sources used are primary data and secondary data with data collection techniques using observation, interview and documentation techniques. And the data analysis techniques in this study are data reduction, data presentation and conclusion drawing.The results of this study are known that (1) in applying for the financing process with certain conditions. (2) the procedure for resolving non-performing financing using the rescheduling policy is to provide invoices, the customer to the BMT As'adiyah Sengkang office, check the completeness of the documents, take a rescheduling policy and make a new agreement. The application of rescheduling at BMT As'adiyah Sengkang is carried out when the third invoice is issued and this is valid for 3 months. (3) the BMT As'adiyah Sengkang streamline the rescheduling policy so that the customer can settle the obligations that have been charged by providing an extension of the installment payment period and reducing the number of installments. However, the rescheduling policy did not have much of an effective effect on problematic murabaha financing, this was proven by the higher NPF (Non Performing Financing) starting from 2017 to 2021.